The contribution of rural social networks to the consolidation of social capital - Castillo, Verenice Sánchez (AWARI, 2023)
This article exhaustively reviews the literature on rural social networks' role in the construction and consolidation of social capital in rural communities. A detailed analysis of case studies and relevant theories examined how these networks, made up of family relationships, friendships, local associations, and community ties, contribute to rural communities' socioeconomic development and well-being. With this objective, a critical and narrative study was developed, with a protocol developed to achieve high methodological rigor. The results highlighted the challenges rural social networks face in the context of urbanization, globalization, and technological change, and how these external influences affect the dynamics and effectiveness of rural social capital. In addition, strategies and policies can strengthen rural social networks and, therefore, social capital, thus facilitating local development and social inclusion. Finally, areas of future research are suggested to understand better the potential of rural social networks in promoting sustainable development and social equity in rural areas.